Development of Clostridium saccharoperbutylacetonicum as a Whole Cell Biocatalyst for Production of Chirally Pure (R)-1,3-Butanediol - Grosse-Honebrink, Alexander; Little, Gareth T.; Bean, Zak; Heldt, Dana; Cornock, Ruth H. M.; Winzer, Klaus; Minton, Nigel P.; Green, Edward; Zhang, Ying (Frontiers in Bioengineering and Biotechnology, 2021)
Chirally pure (R)-1,3-butanediol ((R)-1,3-BDO) is a valuable intermediate for the production of fragrances, pheromones, insecticides and antibiotics. Biotechnological production results in superior enantiomeric excess over chemical production and is therefore the preferred production route. In this study (R)-1,3-BDO was produced in the industrially important whole cell biocatalyst Clostridium saccharoperbutylacetonicum through expression of the enantio-specific phaB gene from Cupriavidus necator. The heterologous pathway was optimised in three ways: at the transcriptional level choosing strongly expressed promoters and comparing plasmid borne with chromosomal gene expression, at the translational level by optimising the codon usage of the gene to fit the inherent codon adaptation index of C. saccharoperbutylacetonicum, and at the enzyme level by introducing point mutations which led to increased enzymatic activity. The resulting whole cell catalyst produced up to 20 mM (1.8 g/l) (R)-1,3-BDO in non-optimised batch fermentation which is a promising starting position for economical production of this chiral chemical.